2022
DOI: 10.1186/s40792-022-01532-4
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic distal gastrectomy for advanced gastric cancer with situs inversus totalis: a case report

Abstract: Background Situs inversus totalis (SIT) is a relatively rare condition, in which the thoracic and abdominal organs are reversed or mirrored from their normal positions. Here, we reported a case of a patient with SIT and advanced gastric cancer with lymph node metastasis who underwent laparoscopic distal gastrectomy (LDG). Case presentation A 67-year-old man with SIT was clinically diagnosed with T3N2M0 advanced gastric cancer located in the middle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(29 reference statements)
0
0
0
Order By: Relevance
“…The most common anomaly observed was that the CHA exited from the superior mesenteric artery, with three cases reported. The solution proposed by Fujita et al [ 24 ] re-confirmed the anatomical landmarks of LND in the suprapancreatic area as the upper borders of the pancreas, portal vein, and left gastric artery from the celiac axis. Therefore, during the preoperative evaluation period, sufficient imaging examination is necessary to detect the normal anatomy and variations in the branching pattern of the celiac trunk, which could significantly reduce the duration of surgery and the intraoperative blood loss.…”
Section: Discussionmentioning
confidence: 98%
“…The most common anomaly observed was that the CHA exited from the superior mesenteric artery, with three cases reported. The solution proposed by Fujita et al [ 24 ] re-confirmed the anatomical landmarks of LND in the suprapancreatic area as the upper borders of the pancreas, portal vein, and left gastric artery from the celiac axis. Therefore, during the preoperative evaluation period, sufficient imaging examination is necessary to detect the normal anatomy and variations in the branching pattern of the celiac trunk, which could significantly reduce the duration of surgery and the intraoperative blood loss.…”
Section: Discussionmentioning
confidence: 98%